Development of Lab-on-a-Disc Integrated with Resazurin-based Assay for Total Bacterial Counting in Raw Milk. Issue 1 (1st January 2022) - Chamnan, Pornthip; Yingkajorn, Mingkwan; Saengdee, Pawasuth; Ranron, Norabadee; Sripumkhai, Witsaroot; Pattamang, Pattaraluck; Jeamsaksiri, Wutthinan; Atthi, Nithi; Vongkamjan, Kitiya
Abstract: The quality of milk and dairy products depends largely on micro-organisms contamination which can pose serious health risks. Therefore, the total viable count (TVC) in raw milk needs to be daily checked to guarantee high quality. A resazurin is used as a dye indicator for the TVC quality in raw milk. However, this method is relatively complicated and inconvenient for on-site measurement. During the wait time, changes in physical and chemical properties of the raw milk were observed and they might affect the accuracy of the test results. Therefore, lab-on-a-disc (LOAD), a low-cost, user-friendly, and fast detection centrifugal microfluidic platform for the TVC test, was proposed in this study. The LOAD device (ϕ: 9.0 cm) was fabricated by laser machining of polymethyl methacrylate (PMMA, acrylic) and assembled with pressure sensitive adhesive (PSA) films. The 10 %(v/v) of resazurin-based assay that incubated at 25 °C was used to detect three different bacterial concentration levels of 4.0 log CFU/mL (low), 6.0 log CFU/mL (medium) and 8.0 log CFU/mL (high) in raw milk. The reduction process changed the color from purple (resazurin) to pink (resorufin) and to white (dihydroresorufin) subsequently. The resazurin and resorufin showed the maximum absorbance at the wavelength of 600 and 570 nm, respectively. After the LOAD was rotated at 5000 rpm for 5 minutes at 25 °C, the color of resazurin in the raw milk with medium and high levels of bacterial concentration started to change from purple to pink at 60 and 15 min, respectively. However, the color of resazurin in raw milk with low level of bacterial concentration remained dark mauve after 120 min. Overall, the LOAD integrated with resazurin-based assay is an alternative method to determine TVC in raw milk and various food stuffs.